Black Flowers. On the floral memorabilia related to the death of Frédéric Chopin from the collection of the Frédéric Chopin Museum in Warsaw - Król, Urszula (Requiem, 2025)
Cyprian Kamil Norwid titled his collection of memoirs relating to his last meetings with six different people (with one exception known to the author personally), Black Flowers. The adjective „black” indicates the mournful and obituary nature of the texts. The title of the work also evokes the custom of bringing flowers to the home of the deceased or to a funeral. Norwid’s work also tells about the need to notice the smallest things, seemingly – insignificant. One of the protagonists of Black Flowers is Frédéric Chopin. The composer’s illness and death, his funeral and posthumous cult are among the key themes of the artist’s biography and legend. Among Chopin’s mementos – first reverently kept by family and friends, and now in museum collections – there are several floral objects related to his death: among them, dried flowers from his deathbed and a posthumous portrait, with his head surrounded by flowers (by painter Teofil Kwiatkowski, a friend of the deceased) found in the collection of the Frédéric Chopin Museum in Warsaw. These items – like the objects and events described in Black Flowers – are seemingly fragile and ephemeral, but in fact imbued with diverse meanings.